An updated synopsis of Aristolochia (Aristolochiaceae, Piperales) in Panama - Gonzalez, Favio; Pabón Mora, Natalia (Instituto de Ecología, A.C., 2018)
Background and Aims: The taxonomy of the Panamanian species of Aristolochia is revised 57 years after the first treatment of the genus for the Flora of Panama. The taxonomic, nomenclatural and chorological novelties of the species present in Panama are updated and discussed with respect to the current infrageneric classification.Methods: Specimens of Aristolochia deposited in 35 herbaria, including specimens collected by the senior author. The type specimens available in JSTOR Global Plants were also examined. A key to the infrageneric groups and species (12 of which are illustrated by photographies) is included.Key results: Four of the 13 species reported in the treatment for the Flora of Panama (Aristolochia arborescens, A. costaricensis, A. sylvicolaand A. veraguensis) are currently reduced as synonyms. A total of 16 species are here reported, two of which (A. cruenta and A. trilabiata) are confirmed as new records for Panama. Aristolochia trilabiata, resurrected here to replace A. didyma, is the first report of this species in Mesoamerica. Here we revalidate Aristolochia schippii, A. sprucei and A. surinamensis, recently reduced as synonyms of A. leuconeura, A. constricta and A. trilobata, respectively. In addition, A. pfeiferi and A. translucida are both confirmed as synonyms of A. tonduzii, and A. gorgona and A. securidata as synonyms of A. grandiflora and A. sprucei, respectively. A total of 13 lectotypes are here designated. Finally, the presence of A. constricta, A. gigantea and A. nummularifolia in Panama is discussed.Conclusions: The Panamanian species of Aristolochia belong to two of the three subgenera: A. panamensis, the only species endemic to Panama, marks the southernmost limit of subgenus Siphisia in the New World. The remaining 15 species belong to the subgenus Aristolochia, series Hexandrae (11 spp.) and Thyrsicae (4 spp.).